On the electrical safety of dielectric elastomer actuators in proximity to the human body. (3rd October 2017) - Pourazadi, S; Shagerdmootaab, A; Chan, H; Moallem, M; Menon, C
Abstract: Novel devices based on the use of dielectric elastomer actuators (DEA) have been proposed for a large variety of different applications. In many of these applications, DEAs are envisioned to be in direct or close proximity to the human body. Since DEAs usually require high voltage for their actuation, the safety of individuals operating or using these devices should be ensured. In this paper, safety standards based on safe limits for electrical discharge are investigated. Flat and cylindrical DEA configurations, which are generally considered as the building blocks for the design of DEA-based systems, are investigated in detail. Relevant elements and factors that affect the electrical discharge of DEA devices are analyzed and guidelines to design DEA-based devices that are not of harm for humans are provided. The performed analyses are experimentally validated using flat DEA samples. The safety requirements that should be considered when wrapping DEAs around the body (specifically the legs) are also briefly investigated to provide a practical example of interest for the biomedical community.